Crazy funny : popular black satire and the method of madness - Guerrero, Lisa (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book examines the ways in which contemporary works of black satire make black racial madness legible in ways that allow us to see the connections between suffering from racism and suffering from mental illness. Showing how an understanding of racism as a root cause of mental and emotional instability complicates the ways in which we think about racialized identity formation and the limits of socially accepted definitions of (in)sanity, it concentrates on the unique ability of the genre of black satire to make knowable not only general qualities of mental illness that are so often feared or ignored, but also how structures of racism contribute a specific dimension to how we understand the different ways in which people of colour, especially black people, experience and integrate mental instability into their own understandings of subjecthood. Drawing on theories from ethnic studies, popular culture studies, cultural studies, psychoanalysis, and trauma theory to offer critical textual analyses of five different instances of new millennial black satire in television, film, and literature - the television show Chappelle's Show, the Spike Lee film Bamboozled, the novel The White Boy Shuffle by Paul Beatty, the novels Erasure and I Am Not Sidney Poitier by Percival Everett, and the television show Key & Peele - Crazy Funny presents an account of the ways in which contemporary black satire rejects the boundaries between sanity and insanity as a way to animate the varied dimensions of being a racialized subject in a racist society"--
Introduction: black raving mad -- "When keeping it real goes wrong": Dave Chappelle, melancholia, and the phenomenology of race -- "The new millennium minstrel show": unmasking blackface and black madness in Spike Lee's Bamboozled -- "The emancipation disintegration": suicidal ideation and black liberation in Paul Beatty's The white boy shuffle -- "I am not myself today.": the spectacularized psychosis of the black subject in Percival Everett's Erasure and I am not Sidney Poitier -- "Talkin' 'bout negrotown": black play, black precarity, and the sovereign black subject in Key & Peele -- Epilogue: unmitigated blackness.
OCLC-licensed vendor bibliographic record.
Keywords: African Americans in mass media; American literature -- African American authors -- History and criticism; Satire, American -- History and criticism; Literature and mental illness -- United States -- History -- 20th century; African Americans -- Race identity; African Americans in popular culture; African Americans and mass media; African Americans -- Intellectual life; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General